The Impact of Instagram Content Formats on User Engagement: An Analytical Study of Ten Cosmetic Brands in Indonesia - Widiarto, Meidira Amalia Putri; Nur Aziza, Nanda Adjeng Castity; Ariadi, Sandi Dwi (Al-MUNZIR, 2024)
Instagram has emerged as a dominant platform in social media marketing, particularly for the cosmetic industry, which thrives on visual and interactive content. With Instagram penetration in Indonesia increasing by 13% from 2022 to 2023, it has become a critical medium for promoting products, monitoring trends, and analysing consumer behaviours. However, a gap remains in understanding how different types of Instagram content influence consumer engagement, especially in the context of cosmetic brands. This research addresses the specific issue of how various content forms, such as images, videos, and interactive campaigns, impact engagement metrics like likes, comments, and shares. By analysing 10 leading cosmetic brands in Indonesia, the study identifies that interactive content, such as influencer collaborations, storytelling, and giveaways, significantly enhances consumer interaction compared to static visuals. The findings offer practical solutions for optimizing social media strategies, enabling brands to build stronger emotional connections with their audiences while improving loyalty and retention. This research contributes to social media marketing literature and provides actionable insights for cosmetic brands to develop data-driven and impactful content strategies in an increasingly competitive market. Keywords: Consumer Engagement, Instagram Marketing, Interactive Content, Cosmetic Industry, Social Media Strategies.